'A rose by any other name': Amplifying Marie Chauvet's Colère in Kettly Mars's Saisons sauvages. Issue 1 (August 2015) - Scott, Lindsey
Abstract : In this article, I argue that Kettly Mars's 2010 Saisons sauvages is in part a rewriting of the second novel in Marie Chauvet's 1968 trilogy Amour, Colère et Folie . I use two of Gérard Genette's theoretical concepts of rewriting to explore the relationship between the two works: accumulation – lengthening of the original text – and clarification – reduction of its opacity. I also observe a unique strategy in Mars's work, obfuscation – reduction in its clarity. Mars's obfuscation of the categories of 'good' and 'bad', by complicating the hero and villain in this rewriting, invites a questioning of the social structures which have created such divides and which continue to contribute to repetitive political instability in Haiti. Ultimately, Mars's retelling of Chauvet's Colère amplifies the original political critique, complicates notions of guilt and innocence, and serves as a reminder of the cyclical nature of Haitian history. However, given the ongoing influence of global imperial powers on Haitian politics and economics, in a sense, this rewriting encourages reflection not only on the political, economic, and social situation in Haiti itself, but also, and perhaps more importantly, on the global forces that have so largely contributed to this repetitive history.